2006
DOI: 10.1002/jctb.1453
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production, immobilization and applications of β‐D‐galactosidase

Abstract: β-D-Galactosidase (β-D-galactoside galactohydrolase, E.C. 3.2.1.23), most commonly known as lactase, is one of the most important enzymes used in food processing, which catalyses the hydrolysis of lactose to its constituent monosaccharides, glucose and galactose. The enzyme has been isolated and purified from a wide range of microorganisms but most commonly used β-D-galactosidases are derived from yeasts and fungal sources. The major difference between yeast and fungal enzyme is the optimum pH for lactose hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
162
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(172 citation statements)
references
References 123 publications
1
162
0
9
Order By: Relevance
“…Notably, the new leader domain (22 aa) has been shown herein to be a new sequence capable of directing secretion of heterologous proteins. This leader domain adds a new feature that can be built into intracellular enzymes that otherwise need to be extracted by cellular disruption using mechanical means or through permeabilization with chemical treatments (Panesar et al, 2006). More importantly, this work will allow for future structural and functional analyses to identify features that contribute to transglycosylation activity and substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the new leader domain (22 aa) has been shown herein to be a new sequence capable of directing secretion of heterologous proteins. This leader domain adds a new feature that can be built into intracellular enzymes that otherwise need to be extracted by cellular disruption using mechanical means or through permeabilization with chemical treatments (Panesar et al, 2006). More importantly, this work will allow for future structural and functional analyses to identify features that contribute to transglycosylation activity and substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…KM402760). β-Galactosidase is considered to be one of the most important enzymes that is widely used in different industries (PIERRE, 2004;PANESAR et al, 2006). It can be found in different groups of microorganisms, plants, and animals, which differ greatly in their properties and structure (PANESAR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Mahoney et al [13] used concentrated whey containing 15% lactose and observed the β-galactosidase activity in the range of 0.039-2.45 U mg -1 using the homogenization with glass beads method. Available literature suggests that chemical methods are ideal for enzyme extraction especially from yeast cells [5]. Although the Toluene -Acetone -Alumina method was effective in release of enzymes, it was not as effective as the SDS-Chloroform method.…”
Section: Impact Of Extraction Methods On β-Galactosidase Activitymentioning
confidence: 99%
“…Although the use of whole cells as a source of β-galactosidase may appear as a good alternative, a major drawback in the use of whole cells is the poor permeability of cell membrane. Different methods such as sonication, use of CTAB, Oxgall, Triton X 100, mixture of SDS -Chloroform, physical disruption etc have been reported in literature [5], it is important to evaluate the ideal method in terms of effi cacy, cost and enzyme yield so that the process could be scaled up to pilot scale and further commercial levels. Although different microbes such as Streptococcus thermophilus, E. coli, Candida pseudotropicalis and Klyuveromyces sp have been studied for production of β-galactosidase at shake fl ask level [6][7][8], yeasts being safe have been extensively exploited for β-galactosidase production.…”
Section: Introductionmentioning
confidence: 99%